SUSTAINABLE HEALTHCARE PRACTICES AT GENERAL HOSPITAL, MAIDUGURI: IMPACT ON PATIENT WELLNESS AND ENVIRONMENTAL RESPONSIBILITY - Maina, Maina Muhammed Bukar; Ahmad, Anas Yunusa Ahmad; Ado, Muhammad Tajuddeen (FUDMA Journal of Sciences, 2025)
Sustainable healthcare delivery is increasingly recognized as essential for improving patient well-being while ensuring environmental responsibility within hospital systems. This study assessed patient satisfaction at General Hospital, Maiduguri, focusing on treatment effectiveness, medical staff professionalism, facility cleanliness, and service delivery speed. A mixed-methods approach was adopted, combining structured questionnaires and semi-structured interviews with patients from Hausari, Bulabilin, and Gwange One—areas with high utilization of the hospital’s services. The findings reveal a generally low level of patient satisfaction, driven by perceived treatment inefficacy, unprofessional staff attitudes, poor hygiene, and prolonged waiting times. These outcomes indicate a significant mismatch between patient expectations and actual healthcare delivery, with implications for both patient wellness and confidence in the public healthcare system. To address these challenges, the study recommends strengthening treatment protocols, instituting continuous professional and interpersonal skills training for healthcare staff, enforcing strict facility sanitation and maintenance standards, and streamlining service delivery processes to reduce delays. Implementing these measures is critical for enhancing patient trust, promoting sustainable healthcare practices, and improving overall service quality at General Hospital, Maiduguri.
Keywords: healthcare sustainability; patient satisfaction; hospital cleanliness; service efficiency; treatment effectiveness